Artificial Intelligence System Integrated With Smartphone Application For Early Detection Of Stunting Based On Toddler Growth Index - Iskandar, Dwi; Putri, Frestiany Regina; Kusuma, Junianto Chandra; Saputro, Rizal Tommy (Institut Teknologi Bisnis AAS Indonesia, 2024)
Toddlers have certain characteristics and needs that require growth monitoring. Toddlers will experience a period called the